Filipino heritage the making of a nation - Roces, Alfredo R. (Felta Multimedia Center, 2004)
"During the postwar years new data about this country have been uncovered, changing, or amending, previous concepts about Filipino history and culture. A fresh viewpoint on the Filipinos and the archipelago they live in was a long felt need. FILIPINO HERITAGE is an attempt at presenting the making of the Filipino nation in the light of the latest findings by the most authoritative scholars on the Philippines and Southeast Asia." -- CD-ROM back cover.